Components and Anti-HepG2 Activity Comparison of Lycopodium Alkaloids from Four Geographic Origins. (28th February 2016) - Tian, Yong-Qiang; Hu, Guang-Wan; Guo, Ming-Quan
Abstract : Lycopodium japonicum Thunb. has attracted great interests due to its rich alkaloids with significant anticancer activity. However, significant chemical differences often exist in a plant species from different geographic origins and affect its quality and bioactivities. Thus, it is urgent to reveal their chemical and biological distinctions at the molecular level. In this context, a comparative chemical analysis of LAs using HPLC-UV-ESI-MS/MS was firstly conducted and resulted in the detection of 46 LAs, 28 of which were identified, and a series of unique LAs markers, such as peaks2, 9, 10, and11, were further found to be characteristic LAs and selected as markers from four different origins for their quality control. In parallel, the comparative bioactivity assay revealed that the total LAs from Hubei province exhibited much higher inhibitory rate at 65.95% against HepG2 cells than those at 26.72%, 20.26%, and 33.62% for Kenya, Guangxi province, and Zhejiang province in China, respectively. To this end, significant chemical fingerprinting differences and discrepancies in bioactivity of LAs were explored firstly, which could provide valuable information for quality control and further activity studies on LAs from different sources and promote their better pharmaceutical applications in the future as well.